Sovereign Bond Market Reactions to Fiscal Rules and No-Bailout Clauses The Swiss Experience - Marc-Daniel Moessinger; Lars P. Feld; Alexander Kalb; Steffen Osterloh (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We investigate the political determinants of risk premiums which sub-national governments in Switzerland have to pay for their sovereign bond emissions. For this purpose we make use of financial market data from 288 tradable cantonal bonds in the period from 1981 to 2007. Our main focus is on two different political influences. First, many of the Swiss cantons have adopted very strong fiscal rules. We find evidence that both the presence and the strength of these fiscal rules contribute significantly to lower cantonal bond spreads. Second, we study the impact of a credible no-bailout regime on the risk premia of potential guarantors. We make use of the Leukerbad court decision in July 2003 which relieved the cantons from backing municipalities in financial distress, thus leading to a fully credible no-bailout regime. Our results show that this break lead to a reduction of cantonal risk premia by about 25 basis points. Moreover, it cut the link between cantonal risk premia and the financial situation of the municipalities in its canton which existed before. This demonstrates that a not fully credible no-bailout commitment can entail high costs for the potential guarantor.
Keywords: E62; G12; H63; 330